Optimized and Approximate Belief Propagation Decoder for Polar Codes - Prasad, V. Hari Krishna; Samson , Mamatha (International Journal of Psychosocial Rehabilitation, 2020)
The polar code is one among the most effective error correcting code, attributable to the channel achieving property. In this paper, we propose an optimized and approximate belief propagation (BP) decoder for polar code for the first time with efficiency in delay. BP decoder is parallel in nature and is more attractive for low-latency applications. Adder is one of the key hardware blocks in BP decoder. By utilizing the approximate computation schemes and by using adders such as ripple carry adder and parallel self timed adder, delay can be reduced. The design is verified and synthesized using Xilinx ISE 14.7